Keadilan Dan Kepastian Hukum (Refleksi Kajian Filsafat Hukum Dalam Pemikiran Hukum Imam SyÃ¢tibÃ®) - Zulfahmi Nur (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2023)
This paper aims to explore the philosophical roots of Syatibi's legal thinking on justice and legal certainty and its relevance to the Indonesian legal state. The theories used in this paper consist of the theory of justice, the theory of legal certainty and the theory of the rule of law. The theory of justice is part of the study of legal philosophy, which Syatibi calls moral and legal integrity. The theory of legal certainty is the basic norms (grundnorm) extracted from Syatibi's works. The method used in this paper is normative juridical with a philosophy of law approach. Philosophy of law is an intellectual activity that thinks rationally, systematically, comprehensively, integrally and critically. The results of the study show that Syatibi, a legal reformer of Granada in the 8th century H/14 AD who is of the Maliki school of thought, has laid the foundation and principles of the rule of law in realising justice and legal certainty through his three monumental works, al-Muwafaqat fi Ushul al-Syari'ah, I'tisam and Fatawa Syatibi. Syatibi's legal philosophy thinking on legal justice is formulated in three legal constructs namely al-maslahah, al-sahl and 'adam al-kharaj. Syatibi formulated legal certainty on five basic legal principles (grundnorm) consisting of: (1), Muqaddimah (preamble), (2). Al-Ahkam (laws), (3). Al-Maqasid (purpose or direction to be achieved), (4). Al-Adillah (legal arguments), and (5). Ijtihad (Legal Reasoning). The idea of the rule of law in the Indonesian context both in the perspective of the rule of law and rechtstaat is dominated by the legal system of Western countries which in general is the idea of the rule of law derived from the results of Western intellectual thought based on liberal and secular philosophies. Law is only limited to positivism, meaning that law is interpreted as an order from the law which results in law only in the form of legal certainty. Positivistic law separates legal justice from legal certainty or separates law from morals. In contrast to the thinking of Islamic legal philosophers such as Shathibi who combines law with justice.